Draft Genome Sequence of an Aeromonas salmonicida subsp. salmonicida Strain from the Canadian Pacific Coast Bearing a Variant of pRAS1 - Vaillancourt, Kevin C. (Microbiol Resour Announc, 2021)
The genome sequencing of Aeromonas salmonicida subspecies salmonicida strain 2004-072 revealed a plasmid bearing a region carrying antibiotic resistance genes very similar to the one found in the plasmid pRAS1, an IncU family plasmid. This new plasmid was named pRAS1b.